Nuclear envelope transmembrane proteins involved in genome organization are misregulated in myotonic dystrophy type 1 muscle - Todorow, Vanessa; Hintze, Stefan; Schoser, Benedikt; Meinke, Peter (Frontiers in Cell and Developmental Biology, 2023)
Myotonic dystrophy type 1 is a multisystemic disorder with predominant muscle and neurological involvement. Despite a well described pathomechanism, which is primarily a global missplicing due to sequestration of RNA-binding proteins, there are still many unsolved questions. One such question is the disease etiology in the different affected tissues. We observed alterations at the nuclear envelope in primary muscle cell cultures before. This led us to reanalyze a published RNA-sequencing dataset of DM1 and control muscle biopsies regarding the misregulation of NE proteins. We could identify several muscle NE protein encoding genes to be misregulated depending on the severity of the muscle phenotype. Among these misregulated genes were NE transmembrane proteins (NETs) involved in nuclear-cytoskeletal coupling as well as genome organization. For selected genes, we could confirm that observed gene-misregulation led to protein expression changes. Furthermore, we investigated if genes known to be under expression-regulation by genome organization NETs were also misregulated in DM1 biopsies, which revealed that misregulation of two NETs alone is likely responsible for differential expression of about 10% of all genes being differentially expressed in DM1. Notably, the majority of NETs identified here to be misregulated in DM1 muscle are mutated in Emery-Dreifuss muscular dystrophy or clinical similar muscular dystrophies, suggesting a broader similarity on the molecular level for muscular dystrophies than anticipated. This shows not only the importance of muscle NETs in muscle health and disease, but also highlights the importance of the NE in DM1 disease progression.